Unobtrusive measures - Webb, Eugene J., 1933-1995.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
This completely rewritten and updated edition builds on the earlier version's drive to justify novel techniques of survey and archival research. The authors combine methods so that research results can withstand the threats to validity.
Previous ed.: published as Nonreactive measures in the social sciences. 2nd ed. 1981.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Electronic books